Small-scale farmers, certification schemes and private standards: Is there a business case? - Kuit, M.; Waarts, Y. (Technical Centre for Agricultural and Rural Cooperation, 2014)
Certification of agricultural products (organic certification, Fairtrade etc.) is often expected to provide a wide array of benefits for small-scale farmers. These include poverty alleviation, reduced environmental impact and food safety. This wide-ranging synthesis of 270 studies presents an analysis of the benefits – but also the costs – of such schemes. Crucially it demonstrates that the decision to invest must be based on sound economic principles. Clearly laid out and argued, the text also provides recommendations to improve the certification business case and impact on smallholders.